Description of the larva of Mnesarete pudica (Hagen in Selys, 1853) (Odonata: Calopterygidae) and notes on known genera of South American Calopterygidae larvae - Guillermo-Ferreira, Rhainer [UNESP]; Bispo, Pitágoras da Conceição [UNESP] (Magnolia Press, 2012)
The final instar larva of Mnesarete pudica is described and illustrated based on reared specimens collected in Brazil. This species can be distinguished from others by presenting: a) five palpal and three premental setae; b) no posterodorsal hooks on abdominal segments; c) lateral spines only in S9-10. M. pudica is compared to other South American calopterygids and biological notes are presented.
Keywords: dragonfly; damselfly; nymph; naiad; taxonomy; Brazil; neotropical